The interaction of human dendritic cells with yeast and germ-tube forms of Candida albicans leads to efficient fungal processing, dendritic cell maturation, and acquisition of a Th1 response-promoting function - Romagnoli, G.; Nisini, R.; Chiani, P.; Mariotti, S.; Teloni, R.; Cassone, A.; Torosantucci, A. (Journal of leukocyte biology, 2004)
T helper cell type 1 (Th1) cell‐mediated immunity plays a rical role in protection against the opportunistic pathogen Candida albicans. Virulence of the fungus is closely associated with its ability to form germ‐tubes (GT), the early phase of the dimorphic transition from the commensal yeast (Y) to the more invasive hyphal (H) form. In this study, we examined the functional outcome of the interaction of Y or GT forms with human dendritic cells (DCs), professional antigen‐presenting cells, which are pivotal for initiation and modulation of T cell responses. DCs phagocytosed and killed Y and GT cells with a comparable efficiency, becoming able to trigger strong proliferative responses by Candida‐specific, autologous T cell clones. Both fungal forms induced DC maturation, as indicated by up‐regulation of CD83, CD80, CD86, CD40, and major histocompatibility complex classes I and II surface antigens. Chemokine receptors were also modulated in Candida–DCs, which showed increased CCR7/CXCR4 and decreased CCR5 expression. Y‐ and GT‐activated DCs differed in the pattern of cytokine expression. In particular, GT cells, in common with fully differentiated H cells, induced significantly more elevated levels of interleukin (IL)‐10 than Y cells. Nevertheless, Y‐, GT‐, or H‐pulsed DCs secreted comparable amounts of IL‐12p70. In addition, irrespective of the fungal form triggering DC activation, Candida–DCs acquired the ability to prime naive T lymphocytes with a defined Th1 phenotype. Overall, our findings highlight the induction of substantially similar functional patterns in human DCs encountering the different forms of growth of C. albicans, both seemingly activating the Th1‐type immunity which is characteristic of the healthy human subjects, naturally immunized and protected against the fungus.